Question and Answers Forum

All Questions      Topic List

Arithmetic Questions

Previous in All Question      Next in All Question      

Previous in Arithmetic      Next in Arithmetic      

Question Number 131525 by mathlove last updated on 05/Feb/21

 if   (a−b)(a+b)=23  then  faind   a∙b=?

if(ab)(a+b)=23thenfaindab=?

Answered by mr W last updated on 05/Feb/21

no unique solution for a,b∈R.  for a,b∈Z:  (a−b)(a+b)=23=1×23  ⇒a−b=1  ⇒a+b=23  ⇒a=((1+23)/2)=12  ⇒b=((23−1)/2)=11  ⇒a×b=12×11=131  or  a−b=−1  a+b=−23  ⇒a=−12  ⇒b=−11  ⇒a×b=131

nouniquesolutionfora,bR.fora,bZ:(ab)(a+b)=23=1×23ab=1a+b=23a=1+232=12b=2312=11a×b=12×11=131orab=1a+b=23a=12b=11a×b=131

Commented by mathlove last updated on 05/Feb/21

thanks

thanks

Commented by Rasheed.Sindhi last updated on 06/Feb/21

Also possible:  a+b=1 ∧ a−b=23       a=12,b=−11       a.b=−132              OR  a+b=−1 ∧ a−b=−23       a=−12,b=11       a.b=−132

Alsopossible:a+b=1ab=23a=12,b=11a.b=132ORa+b=1ab=23a=12,b=11a.b=132

Commented by mr W last updated on 06/Feb/21

correct sir! thanks for remark!

correctsir!thanksforremark!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com